STUDI PENGUKURAN PLACE BRANDING TERHADAP PENINGKATAN KUNJUNGAN WISATA GRAND MAERAKACA DI JAWA TENGAH - Rosita Wulandari; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2020)
Marketing is often equated with branding. However, in fact, marketing and branding are two different concepts, although both of them are strongly related. Branding is an effort to build and communicate the identity and character of brand into society. Branding is not only applied toward product and service but also toward corporate, event, somebody (personal branding), and place. The process of branding is a new paradigm related with how a place must be managed in the future. Tourism branding is one of place brandings that is often discussed as the increasing of society’s awareness of tourism need. This study aims to discover the branding effectiveness in increasing tourist visitation in the Grand Maerakaca Central Java. The method of this study is qualitative descriptive method with questioner and interview as the collecting data techniques. The data collected method uses statistical tools in the form of a questionnaire to make it easier for researchers in the data collection process considering that the research was carried out at the time of the Covid-19 pandemic. This research subjects were taken as many as 100 people calculated based on the Slovin formula according to the number of visitors in 2018. The data sources used were primary data in the form of questionnaires and PT.PRPP internal data, while secondary data were in the form of legislation regarding tourism, Permen PAN RB, and Youth Service data. Sports and Tourism in Central Java Province. The analysis method uses the value of Community Satisfaction Survey accordance with the Regulation of the Minister of State for Administrative Reform and Reform of the Bureaucracy Number 14 Year 2017 with the evaluation framework of place branding effectiveness that is called City Brand Hexagon. The result of the study shows that place branding in Grand Maerakaca runs smoothly. It is because the Grand Maerakaca has a great attraction to be visited by society. Nevertheless, problem is found in The People indicator that is related with disclosure and employee’s friendliness. It is suggested to form Standard Operational Procedure in providing service and periodic performance evaluation